Multicenter Treatment of Ankle Fractures: A Case for the Arthroscopic Evaluation of Ankle Fractures - Jorge I. Acevedo MD; Joseph D. Queen BS; Thomas G. Harris MD; Dominic S. Carreira MD (Foot & Ankle Orthopaedics)
Category: Arthroscopy; Ankle Introduction/Purpose: Although patients treated with open reduction internal fixation of ankle fractures generally recover well with low pain and high function, not all patients who are treated with anatomic open reduction and fixation have excellent results. Several reports describe improved outcomes of arthroscopic assisted treatment compared with open reduction and internal fixation alone.This study aims to report the intraarticular findings and treatment of patients who underwent open reduction internal fixation with arthroscopic assistance from three different centers affiliated with MASTAF, the Multicenter Arthroscopic Study of the Ankle and Foot, and assess the relative rates of pathology by Danis-Weber classification. Methods: Utilizing data from three IRB-approved centers, we investigated the association between intra-articular pathology and patient outcomes in arthroscopically treated ankle fractures. Primary outcome data included patient-reported FAAM scores (ADL, Sports) and VAS pain levels assessed at 1, 2, and 5 years post-op. The three centers involved in the study collected fracture data on 144 patients. All ankle fractures treated by these centers during the time period were treated arthroscopically. We present intra-articular findings for 131 patients, excluding 13 who either sustained work-related injuries or have ongoing litigation. While pre-op X-rays were standard, advanced imaging was employed as deemed necessary. 86 patients whose fractures included a distal fibula component were classified according to the Danis Weber classification system, and pathologies were analyzed with respect to the Weber classification. Follow up data is presented for 45 patients with complete follow up data. All surgeries were performed by fellowship-trained foot and ankle surgeons. Results: Intra-articular pathology was documented in 90.08% of patients, with synovitis (43.51%), deltoid injury (33.59%), and syndesmotic injuries (34.35%) most commonly observed. Osteochondral defects (25.95%), soft tissue impingement (25.95%), and loose bodies (25.19%) were also observed in a significant number of cases. Weber C fractures (n=29) showed significantly higher rates of osteochondral defects (41.38% vs 29.63%) and loose bodies (31.03% vs 16.67%) compared to Weber B fractures (n=54). Weber B fractures had a higher incidence of observed deltoid injury than Weber C fractures (40.74% vs 34.48%) At follow-up, patients reported low pain levels (average VAS: 1.711), great FAAM ADL scores (mean: 87.02) and good FAAM Sports scores (mean: 62.09). Conclusion: While the prevalence of osteochondral defects in ankle fractures has previously been cited as a reason for arthroscopic intervention, our study highlights the substantial prevalence of other pathologies such as loose bodies (33%), synovitis (43.51%), and soft tissue impingement (25.95%). We also identified higher rates of deltoid injury than existing literature (33.59% vs 20%), with the difference being most prominent for Weber B fractures. This, coupled with our positive patient outcomes, suggests that arthroscopy allows for improved detection of intra-articular pathologies during treatment and may aid in the detection of deltoid injuries compared to historical reports.